Heat stress inhibits the proliferation and differentiation of myoblasts and is associated with damage to mitochondria - Lu, Jiawei; Li, Huixia; Yu, Debing; Zhao, Peng; Liu, Yuan (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Heat stress is harmful to the health of humans and animals, more and more common, as a consequence of global warming, while the mechanism that heat stress modulates skeletal development remains unknown. Hence, we conducted a model of heat stress in vitro. Methods: We used Hu sheep myoblasts as the research object, real-time quantitative PCR (RT-qPCR) and western blot (WB) were conducted to detect the expression of mRNA and protein in heat-stressed myoblasts. The would-healing assay was used to detect the migration of myoblasts. The mitochondria were observed by a transmission electron microscope. Results: mRNA and protein expression of HSP60 was significantly enriched in the heat-stressed myoblasts during proliferation and differentiation (p < 0.05). In our study, we indicated that heat stress enriched the intracellular ROS of the myoblasts (p < 0.001), leading to an increase in autophagy in the myoblasts to induce apoptosis. The results demonstrated that the protein expression of LC3B-1 and BCL-2 was significantly increased in myoblasts under heat stress during proliferation and differentiation (p < 0.05). Additionally, heat stress inhibited mitochondrial biogenesis and function and reduced the mitochondrial membrane potential and downregulated the expression of mtCo2, mtNd1 and DNM1L (p < 0.05) in myoblasts during proliferation and differentiation. Consequently, heat stress inhibited the proliferation and differentiation of the myoblasts, in accordance with the downregulation of the expression of PAX7, MYOD, MYF5, MYOG and MYHC (p < 0.05). Moreover, heat stress also inhibited the cell migration of the myoblasts. Discussion: This work demonstrates that heat stress inhibits proliferation and differentiation, and accelerates apoptosis by impairing mitochondrial function and promoting autophagy, which provides a mechanism to understand heat stress affects the development of the skeletal muscle.